Yarrowia lipolytica: A model and a tool to understand the mechanisms implicated in lipid accumulation - Beopoulos, Athanasios; Chardot, Thierry; Nicaud, Jean-Marc (Biochimie, 2009)
The oleaginous yeast Yarrowia lipolytica is known to inhabit various lipid-containing environments. One of the most striking features in this yeast is the presence of several multigene families involved in the metabolic pathways of hydrophobic substrate utilization. The complexity and the multiplicity of these genes give Y. lipolytica a wide capability range towards hydrophobic substrate (HS) utilization and storage. The combination of the increasing knowledge of this yeast's metabolism and the development of more efficient genetic tools is offering new perspectives in using Y. lipolytica as a model organism to study the mechanisms involved in lipid metabolism associated to fat uptake, storage, deposition, mobilization and regulation. Nutrient status and culture conditions seem to play a major role in obesity.